Schizophrenia, Not a Psychotic Disorder: Bleuler Revisited - Loch, Alexandre Andrade (Frontiers in Psychiatry, 2019)
Current diagnostic criteria delineate schizophrenia as a discrete entity essentially defined by positive symptoms. However, the role of positive symptoms in psychiatry is being questioned. There is compelling evidence that psychotic manifestations are expressed in the population in a continuum of varying degrees of severity, ranging from normality to full-blown psychosis. In most cases, these phenomena do not persist, but they constitute risk factors for psychiatric disorders in general. Psychotic symptoms are also present in most non-psychotic psychiatric diagnoses, being a marker of severity. Research revealed that hallucinations and delusions appear to have distinct, independent biological underpinnings—in the general population, in psychotic, and in non-psychotic disorders as well. On the other hand, negative symptoms were seen to be far more restricted to schizophrenia, have other underlying pathophysiology than positive symptoms, predict outcome and treatment response in schizophrenia, and start before the first psychotic outbreak. The current work discusses the concept of schizophrenia, suggesting that a greater emphasis should be put on cases where psychotic symptoms emerge in a premorbid subtly increasing negative/cognitive symptoms background. In those cases, psychosis would have a different course and outcome while psychosis occurring in the absence of such background deterioration would be more benign—probably having no, or a milder, underlying degenerative process. This reformulation should better drive psychopathological classification, face positive symptoms as epiphenomenon of the schizophrenia process, and dishevel stigma from schizophrenia and from delusions and hallucinations.